The Effect Of Customer Experience And Service Quality On Consumer Satisfaction Users Of Maxim Transportation Services At Makassar City - Musdalifa Marhabang; Haedar Akib; Didin Halim (Public Resource Innovation Management and Excellence, 2024)
This study aims to determine the description and influence of consumer experience and service quality either partially or simultaneously on consumer satisfaction of Maxim transportation service users in Makassar City. To achieve this goal, the researchers used indicators to measure these variables. The indicators of consumer experience variables include sensory experience, emotional experience, cognitive experience, physical experience and social experience. Indicators of service quality variables include physical evidence, reliability, responsiveness, assurance and empathy. The indicators of consumer satisfaction variables include re-purchase (re-purchase), creating word of mouth, creating a brand image, and creating purchasing decisions at the same company. The research method used is a quantitative method. The sample used is the sample formulated by Slovin as many as 100 respondents, with data collection namely documentation studies and questionnaires that are tested for validity and reliability. The data obtained were processed using data analysis and the help of SPSS version 25 program which consisted of classical assumption test, multiple linear regression analysis, t test, F test and coefficient of determination. The results showed that the variables of consumer experience and service quality had a significant effect partially or simultaneously on consumer satisfaction of Maxim transportation service users in Makassar City, this was shown based on the t test and F test. The results of the coefficient of determination test showed that consumer experience and service quality had an effect. by 55.5% of the consumer satisfaction of Maxim transportation service users in Makassar City.